What you have to do in such a case, is to muliply each term of each factor by each term of other factors. As ax+bx = (a+b)x, (a+b)(x+y) = (a+b)x+(a+b)y = ax+bx+ay+by, so (a+b)(x+y) = ax+ay+bx+by.
Here, one way is to first distribute 5x and -8, which means that
(6x2-4x+11)(5x-8) = 5x(6x2-4x+11)-8(6x2-4x+11), then multiply 5x by 6x2, by -4x and by 11, and multiply -8 by each term too. You'll have 5x(6x2-4x+11)-8(6x2-4x+11) = 30x3-20x2+55x-48x2+32x-88.
Finally, add the coefficients of each degree of x to have 30x3-68x2+87x-88
(6x2-4x+11)(5x-8) = 30x3-68x2+87x-88